Impact of Operating Cash Flow on Stock Returns - Bonifacius Parlin Sumarlin Malau; Ignatius Oki Dewa Brata (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
In this research, researchers aspire to examine the theory of whether there is a cash flow effect on stock changes. Stock returns which are used as stock measurement tools are a reflection of market reactions to what happens within the company in terms of fundamentals. Therefore, to measure the fundamental factors that exist within the company researchers utilise operating cash flow. Operating cash flow is seen as being able to represent because operating cash flow data exists in every company. Moreover, hence that the comparison is balanced the researchers choose to use the population of companies in the LQ 45 area. After being tested using simple linear regression, the results are as previously thought that there are influences on the company's Fundamental factors which in this study is the Operating Cash Flow with market factors which in this study represented by Stock Return.